2021
DOI: 10.1038/s41598-021-86788-w
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of zearalenone elevated colon cancer cell growth through G protein-coupled estrogenic receptor

Abstract: Colon cancer is one of the leading causes of cancer death worldwide. It is widely believed that environmental factors contribute to colon cancer development. Zearalenone (ZEA) is non-steroidal estrogenic mycotoxin that is widely found in the human diet and animal feeds. Most cancer studies of ZEA focused on estrogen sensitive cancers, while few focused on other types, such as colon cancer; despite the gastrointestinal tract being the first barrier exposed to food contaminants. This study investigated the stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Automatic cell counters have been developed and are commercially available. The LUNA TM system (LOGOS BIOSYSTEMS) used in [4][5][6] requires 10 µL of cell solution. It is based on conventional imaging and image processing is used to count the imaged cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automatic cell counters have been developed and are commercially available. The LUNA TM system (LOGOS BIOSYSTEMS) used in [4][5][6] requires 10 µL of cell solution. It is based on conventional imaging and image processing is used to count the imaged cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this expression, represent the absorption spectrum expressed in percentage. It is now straightforward to deduce:(4) …”
mentioning
confidence: 99%
“…Recent studies have reported that in HT29 and SW480 colorectal cancer cell lines, ZEN (3 μM) treatment can promote G-protein-coupled ER 1 and activate its downstream parallel signaling pathways MAPK and Yap1/TAZ, thereby promoting cell proliferation. 122…”
Section: The Mechanism and Pathway Of Zen-induced Toxicity In Vivomentioning
confidence: 99%
“…In addition to aflatoxin, many other toxins have been identified as having carcinogenic activity such as fumonisins, ochratoxins, trichothecenes, and zearalenone [ 136 , 137 ]. Kwan Lo et al recently showed that low-dose zearalenone stimulated colon cancer cells in vitro through a G-protein-coupled estrogenic receptor [ 138 ]. Furthermore, zearalenone causes decreased expression of tight junction proteins with subsequent gut barrier dysfunction as well as gut bacterial dysbiosis [ 139 ].…”
Section: Mycobiomementioning
confidence: 99%